ANTIHYPERTENSIVE EFFECT OF THE PUNICA GRANATUM JUICE IN DEOXYCORTICOSTERONE ACETATE–SALT MODEL OF HYPERTENSION IN RATS - Pankaj M, Chaudhari; Dheeraj T, Baviskar; Sachin N, Mahajan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Hypertension an important global health challenge is the prevalent cause of cardiovascular disease. Natural products are emerging as new therapeutic tools in the management of hypertension due to side effects and the patient’s adherence of the existing treatments. In the present study, we investigated the antihypertensive effect of the Punica granatum juice in deoxycorticosterone acetate (DOCA)â€“salt model of hypertension in rats. Methods: Antihypertensive activity was evaluated in P. granatum juice extract (PGJ) (PJ-100 mg/kg and 300 mg/kg; p.o.) for 4 weeks in DOCA treated rats. Blood pressure by non-invasive (indirect) method and invasive method was measured. Further, vascular reactivity to noradrenaline (1 Î¼g/kg), adrenaline (1 Î¼g/kg), phenylephrine (1 Î¼g/kg), serotonin (1 Î¼g/kg), and angiotensin II (25 ng/kg) was recorded. Antioxidant studies such as thiobarbituric acid reactive substances (TBARS); while enzyme activity of superoxide dismutase (SOD), catalase (CAT), and glutathione reductase (GSH) in kidney tissue was also carried out. Results: Administration of PGJ (PJ-100 mg/kg and 300 mg/kg; p.o.) for 4 weeks in DOCA treated rats significantly (p<0.05) reduced the mean arterial blood pressure and vascular reactivity changes to various catecholamines. PJ treatment significantly (p<0.05) decreased the levels of TBARS; while enzyme activity of SOD, CAT, and GSH in kidney tissue was significantly increased. Conclusion: Results of the present work suggest that PGJ has an antihypertensive action in unilateral nephrectomized DOCA-salt hypertensive rats and could be possible starting point for treatment of hypertension with increased patient adherence.